2015
DOI: 10.7251/bii1501028s
|View full text |Cite
|
Sign up to set email alerts
|

Classification of patients at risk for chronic kidney disease by use of eGFR and albuminuria

Abstract: SummaryIntroduction. Screening for chronic kidney disease (CKD) has been advised in high-risk populations. However, data on the prevalence of early asymptomatic stages vary and depend on the definition of CKD. In the present study subjects at risk for CKD (patients with diabetes mellitus type 2-DM2, with hypertension and older than 60 years without diabetes and hypertension) were classified in categories defined by eGFR and albuminuria staging system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, many other factors influence the rate of progression, including age, co-morbid conditions, such as diabetes mellitus or hypertension, race, ethnicity and genetic mutations. 37,38 Nonetheless, these factors do not account for the observed variability in kidney disease progression. 39,40 While comparing the percentages of people residing in rural regions and the main urban region, it was observed that CKD cases in some rural regions appear to be under represented.…”
Section: Discussionmentioning
confidence: 99%
“…However, many other factors influence the rate of progression, including age, co-morbid conditions, such as diabetes mellitus or hypertension, race, ethnicity and genetic mutations. 37,38 Nonetheless, these factors do not account for the observed variability in kidney disease progression. 39,40 While comparing the percentages of people residing in rural regions and the main urban region, it was observed that CKD cases in some rural regions appear to be under represented.…”
Section: Discussionmentioning
confidence: 99%